2016
DOI: 10.11114/aef.v3i1.1317
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Foreign Direct Investment (FDI) on Economic Growth in Eastern Africa: Evidence from Panel Data Analysis

Abstract: This study has analyzed the impact of Foreign Direct Investment (FDI) on Economic growth in 14 Eastern Africa countries by employing 34 years (1980-2013) panel data, using dynamic GMM estimators after checking for autocorrelation and model specification tests. Developing countries have been attracting FDI attempting to reduce resource gaps, technology gap, unemployment and trade deficits. However, unlike classical growth theories, the empirical studies sought inconclusive effect of FDI on growth. The findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 46 publications
7
39
0
4
Order By: Relevance
“…The author reported that aggregate FDI had a very significant impact on economic growth in Zimbabwe, using a multiple regression model. Zekarias (2016) also found a positive correlation between FDI and economic growth concluding that FDI was cardinal for growth of these countries and therefore need to attract more. It is noteworthy that few studies in the literature could not support the above findings.…”
Section: Discussion Of Estimation Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The author reported that aggregate FDI had a very significant impact on economic growth in Zimbabwe, using a multiple regression model. Zekarias (2016) also found a positive correlation between FDI and economic growth concluding that FDI was cardinal for growth of these countries and therefore need to attract more. It is noteworthy that few studies in the literature could not support the above findings.…”
Section: Discussion Of Estimation Resultsmentioning
confidence: 91%
“…The implication was that unless the Zambian government considers reforming policies, FDI will not serve as the prelude for the desired economic growth. Zekarias (2016) analyzed the impact of FDI on Economic growth in 14 Eastern Africa countries by employing 34 years (1980-2013) panel data, using dynamic GMM estimators after checking for autocorrelation and model specification tests. The findings confirm that FDI is a key deriver of economic growth and a catalyst to economic conditional convergence in Eastern Africa; so, the sub-region needs to attract more FDI by improving investment environment, strengthening regional integration, developing human capital and basic infrastructure, and promoting export-oriented investment.…”
Section: Effect Of Fdi and Host Country Economic Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Angola's outflow of investments, primarily by the government-owned petroleum and natural gas MNE Sonangol, expanded by 35 percent to $10.7 billion [11]. Moreover, the outflow of FDI is mostly seen from the Sub-Saharan African countries with less impact from the countries in the northern part of the continent [12]. The table below shows the outflow of FDI from the sub-regions on the African continent.…”
Section: F Outward Foreign Direct Investment In Africamentioning
confidence: 99%
“…In empirical studies conducted in different countries or country groups within the scope of the cross section, time series and panel data analysis methodology since 1990s, it is reached the end of the long termed effects of foreign direct investments inflows in capital importer countries on real GDP generally positive and statistically significant. (Balasubramanyam et al, (1996), Borensztein et al, (1998), Bosworth andCollins (1999), De Mello (1999), Obwona (2001), Kumar and Pradhan (2002), Hermes and Lensink (2003), Li and Liu (2004), Khawar (2005), Lensink and Morrisey (2006), Alfaro and Charton (2007), Mun et al, (2008), Chowdhary and Kushwaha (2013), Zekarias (2016)). These results most of which were obtained from studies conducted in developing countries empirically bear the thought of the foreign direct investment inflows have positive effects on economic growth of capital importer countries as is predicted in theoretical framework out.…”
Section: Literature Summary and The Position Of The Research In Litermentioning
confidence: 99%